P5 Effect of nasm corrective exercises on functional movement patterns, sensorimotor function, & fatigue in collegiate athletes with functional ankle instability. (17th September 2017) - Bagherian, S; Rahnama, N; Wikstrom, EA; Rostami, F
Abstract : Study Design: Randomised controlled trial. Objectives: To investigate the effect of National Academy of Sport Medicine (NASM) corrective exercises on functional movement patterns, sensorimotor function, and fatigue sensitivity in collegiate athletes with functional ankle instability (FAI). Background: Altered movement patterns, sensorimotor dysfunction and an increased sensitivity to fatigue have all been identified in chronic ankle instability patients. Methods and Measures: Forty-six male volunteers were randomly assigned to the experimental (n=23) or control (n=23) group. Participants in the experimental group performed supervised corrective exercises three times per week for 8 weeks. All functional movement patterns (double limb squat, double limb squat with heel lift and single limb squat) and sensorimotor outcomes (static and dynamic postural control, strength, and joint position sense) were assessed with and without fatigue before and after the intervention. Forty participants finished the intervention program and were included in the final analysis. Results: Significant group ×time interactions demonstrated improvements functional movement patterns and sensorimotor function in the experimental group relative to the control group (p<0.001), in a non-fatigued state. However, non-significant group ×time interactions were found for all variables in the fatigued state (p>0.05) except static postural control (p<0.016). Conclusion: These findings demonstrate that 8 weeks of NASM corrective exercises is effective at enhancing functional movement patterns and sensorimotor function in collegiate athletes with FAI. However, this intervention program has limited abilities at reducing the effects of fatigue.